Modeling multiphase materials processes gas-liquid systems - Iguchi, Manabu (Springer, 2011)
Quot;Modeling Multiphase Materials Processes: Gas-Liquid Systems" describes the methodology and application of physical and mathematical modeling to multi-phase flow phenomena in materials processing. The book focuses on systems involving gas-liquid interaction, the most prevalent in current metallurgical processes. The performance characteristics of these processes are largely dependent on transport phenomena. This volume covers the inherent characteristics that complicate the modeling of transport phenomena in such systems, including complex multiphase structure, intense turbulence, op.